Exploring The Mediating Effect of Work Ethics on The Relationship Between Organizational Culture And Managerial Efficiency - Alkipsy, Ensejam Ibrahim Hashem; Raju, Valliappan (International Journal of Psychosocial Rehabilitation, 2020)
In the field of organizational behavior, many researchers agreed that a strong link exists between managerial efficiency and organizational culture. Furthermore, they argued that differences in cultures and countries should be taken into consideration as managerial efficiency is predominately culture specific. Thus, the objective of this study is to examine the mediating effect of Work ethics on the relationship between organizational culture and managerial efficiency in the oil and gas industry in Yemen. The study employed a cross-sectional research design based on a systematic random sampling technique on 357 administrative employees in the oil and gas industry in Yemen. The data obtained was analyzed using structural equation modeling technique with the aid of SmartPLS version 3.0. The study result shows that there is significant positive relationship between organizational culture and managerial efficiency (β = 0.095, SE= 0.065, t = 3.112, p< 0.10). Also, Work ethics mediate the relationship between organizational culture and managerial efficiency, as the interaction between organizational culture and Work ethics in predicting managerial efficiency was significant (β = 0.140, SE = 0.113, t = 1.50, p< 0.10). Thus, based on these findings, it is recommended that management could enhance the efficiency of managers at both high and lower level by encouraging an organizational culture that promotes creativity and innovation. Also, integrating Work ethics values into the organization could foster managerial efficiency through positive work outcomes.